1997
DOI: 10.1002/(sici)1097-4636(19970615)35:4<513::aid-jbm11>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and development of RGD‐peptide‐modified poly(lactic acid‐co‐lysine) as an interactive, resorbable biomaterial

Abstract: The design of biomaterials containing specific ligands on the surface offers the possibility of creating materials that can interact with and potentially control mammalian cell behavior. Biodegradable materials further provide the significant advantage that the polymer will disappear in vivo, obviating long-term negative tissue responses as well as the need for retrieval. In earlier studies we synthesized and characterized arginine-glycine-aspartic acid (RGD) peptide-modified poly(lactic acid-co-lysine) (PLAL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 0 publications
0
115
0
3
Order By: Relevance
“…Bulk modification is typically realized by copolymerization or functional group attachment to the polymer chain before scaffold fabrication. For example, Langer's group synthesized poly(L-lactic acid-co-L-lysine) and chemically attached RGD peptide to the lysine residue of the copolymer to enhance cell adhesion [113,114]. However, bulk chemical modification usually changes the processing and mechanical properties of the polymers, which often is a disadvantage.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Bulk modification is typically realized by copolymerization or functional group attachment to the polymer chain before scaffold fabrication. For example, Langer's group synthesized poly(L-lactic acid-co-L-lysine) and chemically attached RGD peptide to the lysine residue of the copolymer to enhance cell adhesion [113,114]. However, bulk chemical modification usually changes the processing and mechanical properties of the polymers, which often is a disadvantage.…”
Section: Surface Modificationmentioning
confidence: 99%
“…RGD sequences present on peptide amphiphiles [349], hyaluronan hydrogels [350], dextran [351], collagen [352], poly-l-lysinegraft-(polyethylene glycol) copolymers [353], poly(lactic acid-co-lysine) [354], poly(ethylene glycol)-poly(lactic acid) diblock copolymers [355], acrylic terpolymers [356], and polyurethanes [357] have been reported to promote cell adhesion to a variety of cell types, including neurons [353,358], osteoblasts [359,360], endothelial cells [361], and fibroblasts [350]. In some cases, the RGD sequences can also promote other cellular functions such as matrix mineralization of osteogenic cells [359,360] and neurite outgrowth [358].…”
Section: Micro-and Nano-structures-mentioning
confidence: 99%
“…Myc/c-myc (EQKLISEED) 10 aa Antibody • Ligand density characterization of peptide-modified biomaterials [371] • Biomimetic peptides [359,372] • The effect of peptide surface density on mineralization of a matrix deposited by osteogenic cells [359,360] • Enhancement of the growth of human endothelial cells by surface roughness at nanometer scale [361] • Adhesion of α 5 β 1 receptors to biomimetic substrates constructed from peptide amphiphiles [349] • Biomimetic peptide surfaces that regulate adhesion, spreading, cytoskeletal organization, and mineralization of the matrix deposited by osteoblast-like cells [359,360] RGD-linked polymers • RGD-peptide-modified poly(lactic acid-co-lysine) [354] • Acrylic terpolymers with RGD peptides [356] • Diblock copolymers modified with cyclic RGD peptides [355] • Polyurethanes [357] • Synthetic hydrogels [350,363,370] • Immobilized RGD peptides on surface-grafted dextran [351] • Collagen by covalent grafting with RGD peptides [352] • Hyaluronan hydrogel [350] • RGD-grafted poly-l-lysine-graft-(polyethylene glycol) copolymers block [353] • Neurite outgrowth on well-characterized surfaces [ • Neuronal cell attachment [10] • Immobilization of laminin peptide in molecularly aligned chitosan by covalent bonding [11] …”
Section: Tagmentioning
confidence: 99%
“…Cell integrins are transmembrane proteins on the cell surface that adhere to the proteins of the ECM such as collagen, fibronectin, or vitronectin. These and other adhesive proteins contain short peptide sequences such as RGD, REDV, YIGSR, PHSRN, KNEED, and PRRARV, [37][38][39][40][41][42][43][44][45][46][47][48][49] which are bound by the integrins to promote cell adhesion, spreading, and proliferation. Although significant work has been done to attach proteins and peptides to metal oxide particles 21 and silicon oxide on Si wafers, 26 relatively little research has been reported on attachment of polypeptides to macroscopic metallic surfaces.…”
Section: Introductionmentioning
confidence: 99%